Lysosomal degradation of newly formed insulin granules contributes to β cell failure in diabetes - Adrien Pasquier (Nature Portfolio, 2019)
Impaired beta-cell insulin secretion is a key pathological feature of type 2 diabetes. Here, the authors describe metabolic stress induced lysosomal degradation of newly formed insulin granules, independent of macroautophagy, as a potential mechanism for beta-cell dysfunction.